THE INFLUENCE OF TRAINING AND ORGANIZATIONAL CULTURE ON EMPLOYEE PERFORMANCE THROUGH COMPETENCE AS A MEDIATING VARIABLE AT PT BANK BJT: THE INFLUENCE OF TRAINING AND ORGANIZATIONAL CULTURE ON EMPLOYEE PERFORMANCE THROUGH COMPETENCE AS A MEDIATING VARIABLE AT PT BANK BJT - Oktori, Oktori; Yusuf, M. (Yayasan Pusat Cendekiawan Intelektual Nusantara, 2025)
Human Resources (HR) is one of the very important factors that cannot be separated from the continuity and success of an organization, be it a government institution, social institution, or company, because basically Human Resources include individuals who are employed and empowered in the organization, who have a role as strategic planners, operational implementers, as well as the main drivers in every organizational activity in order to realize the vision, mission, and short-term and long-term goals that have been set. The purpose of this study is to determine the positive influence between training variables, organizational culture, on employee performance through competence as a mediating variable on employees of PT. Bank JTrust Indonesia Tbk. The research method used is associative research with a quantitative approach. Sampling in this study used a sample of 70 respondents. The data collection method used is a questionnaire, while the data analysis used in this study was carried out with validity tests, reliability tests, Inner Model: R-Square tests, F-Square tests, and hypothesis tests. for the Performance variable is 0.944 or 94.4%, which indicates that Training, Organizational Culture and Competence contribute 94.4% to Employee Performance, this shows that the contribution is in the substantial (significant) category, while the rest, namely 5.6% is contributed by other independent variables that are not disclosed in this research.